The effects of combined vitamin C and vitamin E in streptozotocin-induced diabetic rat kidney - Kukner, Aysel; Colakoglu, Neriman; Ozogul, Candan; Naziroglu, Mustafa; Firat, Tulin (My University, 2009)
Diabetic nephropathy is a serious complication of diabetes mellitus. Oxidative stress has been suggested to play a key role in the pathogenesis of diabetic nephropathy. Vitamins C and E play important roles in the antioxidant defense system. It is likely that both vitamins act in a synergistic manner, with vitamin E primarily being oxidized to the tocopheroxyl radical and then reduced back to tocopherol by vitamin C. The purpose of the study was to determine the effects of supplementation of Vitamins C and E (VCE) on diabetic rat kidney. Adult female Wistar rats were used in the study. The animals were divided into three groups. Group I: the control group; Group II: diabetic group, streptozotocin (40 mg kg-1) was administered group; Group III: diabetes + VCE group, received a diet containing a combination of ascorbic acid and dl-?-tocopheryl acetate per kg of feed. Rats were killed on 21st day and renal tissues were taken and fixed in 2.5% glutaraldehyde solution for electron microscopic examination. When compared with the control group, congestion of the glomerular capillaries, increased mesangial cells and distinct mesangium, shortened podocyte processes and disappearance of filtration slit pore of diabetic rat kidney were observed. In the group treated with VCE, glomerular changes were less distinct than the diabetic group. Lengths of the pedicles were similar to the control group. VCE reduced the changes in the glomerular structures due to diabetes. © Medwell Journals, 2009.
Keywords: Diabetes; Kidney; Oxidized; Renal; Tissue; Ultrastructure; Vitamin C and E